Pengembangan Jobsheet pada Proses Pembelajaran Praktek Mesin Listrik untuk Mahasiswa Teknik Elektro - Larra Oktavia; Muldi Yuhendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
The practice of electrical machines is one of the learning activities for undergraduate students of Electrical Engineering Education which is carried out in the form of practice in the laboratory. This practical activity requires a worksheet as a guide for students to practice. Based on the observations made, the jobsheets used in the electrical machine practice activities for undergraduate students of Electrical Engineering Education, Padang State University need to be developed to suit the practical material contained in the new curriculum. Therefore, in this study, a valid and practical electric machine practice worksheet was developed in accordance with the curriculum for Electrical Engineering Education students. The development of the jobsheet is carried out using the 4D development research method, which consists of four stages of activity, namely the define, design, develop, and dessiminate stages. The feasibility of the developed jobsheet is reviewed from the validity and practicality of the jobsheet. The data analysis technique in this research is descriptive quantitative. The results of data analysis showed that the worksheets developed in this study were suitable for use with 93% validity from experts and 94% practicality from jobsheet users in the very practical category, while student respondents were 75.6% in the practical category.